Once more on Chunuk Bair : the Anzacs return to Gallipoli 1918-1919 : a thesis presented in partial fulfilment of the requirements for the degree of Master of Arts in History at Massey University, Manawatū, New Zealand - Johns, Rebecca Cora (Massey University, 2018)
There has been much said about almost every facet of the Gallipoli campaign. It has been an enduring favourite topic of many scholars, even more so with the 100th anniversary just passed. Every aspect of the military campaign has been scrutinised, the attitudes of the men analysed, and the decisions of the leadership criticised. It would seem at face-value, there is little left to add to the discussion surrounding Gallipoli. It has long been acknowledged that this battle saw New Zealand, alongside Australia, step on to the word stage as a separate entity to the British Empire – and thus Anzac became synonymous with Gallipoli. Anzac has come to stand for much more than just the Australian and New Zealand Army Corps; it is a spirit and tradition. This was readily recognised when, after the Armistice of Mudros, the Canterbury Mounted Rifles, NZEF and 7th Light Horse Regiment, AIF were chosen to return to the Dardanelles as a part of the wider occupation of Turkey. During this return to Gallipoli, the Canterbury Mounted Rifles and 7th Light Horse took part in a reconnaissance of the Peninsula, and the Canterbury Mounted Rifles worked to identify and rebury the dead from the 1915 battle. The reverence with which this was done, and the fascination these Anzacs displayed when they patrolled the old battleground - shown in the photographs captured during their stay - indicates just how significant Gallipoli has always been as a physical space and a memory. Immediately after the Canterbury Mounted Rifles and 7th Light Horse left, the Australian Historical Mission led by Charles Bean arrived. The images captured by this team help provide a broader context for those captured by the Canterbury Mounted Rifles. The words of journalist Ernest Peacock, embedded with the 7th Light Horse, similarly provide framework for the photographs, as well as giving some information as to how this return to Gallipoli was seen from the home fronts of New Zealand and Australia. The Anzacs’ first pilgrimage to Gallipoli marked the beginning of a long-standing tradition that marks the birth of our nations.
The following figures in the thesis have been reproduced with the written permission of the National Army Museum New Zealand (NAM), the Australian War Memorial (AWMM), and the Marlborough Museum: Figure 1 (p. 17) Landing at Maidos, Gallipoli. Trooper Leonard William Mowat, NAM, 1992.745.3. https://nam.recollect.co.nz/nodes/view/4553 Figure 2 (p. 24) Photograph of Private William Thomas Dundon’s grave at Shrapnel Valley Cemetery, Gallipoli. Marlborough Museum. 2002.092.0037. Figure 3 (p. 26) A carved headstone commemorating dead members of the CMR. Trooper Mowat, 1992.745.4, NAM. https://nam.recollect.co.nz/nodes/view/4761 Figure 5 (p. 29) Anzac Cove, Australian Historical Mission. G01747, AWMM. Figure 6 (p. 31) Anzac Cove, Trooper Mowat, 1992.745.4, NAM. https://nam.recollect.co.nz/nodes/view/4753 Figure 7 (p. 33) Turkish Monument on Russel Top, Trooper Mowat, 1992.745.4, NAM. https://nam.recollect.co.nz/nodes/view/4765 Figure 8 (p. 34) Turkish Monument, Historical Mission, G01743, AWMM. Figure 9 (p. 36) Lone Pine, Historical Mission, G01751, AWMM. Figure 10 (p. 37) Rhodondendron Ridge looking to Chunuk Bair, Trooper Mowat, 1992.745.4, NAM. https://nam.recollect.co.nz/nodes/view/4771 Figure 11 (p. 38) Member of the Historical Mission standing in a shell hole. G01962, AWMM. Figure 12 (p. 38) Members of the CMR on a Turkish naval gun. Trooper Mowat, 1992. 745.4, NAM. https://nam.recollect.co.nz/nodes/view/4775
Keywords: Bean, C. E. W. (Charles Edwin Woodrow), 1879-1968; Peacock, Ernest (Journalist); Australian Historical Mission; New Zealand. Army. Canterbury Mounted Rifles Regiment; Australia. Australian Army. Light Horse Regiment, 7th; Gallipoli Peninsula (Turkey) -- History, Military -- 1918-1919